Effectiveness of blending E-learning with field trip on Chinese herbal medicine education: quasi-experimental study - Lei Li; Chi Wing Tam; Ning Wang; Fan Cheung; Qing Zhou; Cheng Zhang; Chien-shan Cheng; Lei Xiong; Yibin Feng (BMC, 2020)
Abstract Background Chinese Medicine education is part of professional medical training in Hong Kong. An important element of this is herbal medicine, which requires both theoretical and practical knowledge. A field trip programme was adopted to provide students with direct experience of medicinal plants studied in lectures. However, problems with the current programme were identified in learning outcome assessment and long-term knowledge management. To improve the teaching quality, a Moodle e-learning module was designed for augmentation. This study aimed to quantitatively evaluate the effectiveness of the Moodle module in supplementing the current field trip programme. Methods Prospective quasi-experiment. Participants were 49 year-2 students in the Bachelor of Chinese Medicine programme. A Moodle module including five online activities regarding two groups of herbal plants was integrated before and after the field trip. Fill-in-the-blank questions were used to assess the learning outcome. Also, a questionnaire was developed to collect student feedback as the secondary outcome. Results For herbal plants in Group A, the assessment score was higher in Moodle group (29.65 ± 5.0) than for the control group (21.65 ± 6.5) (P <  0.01). For herbal plants in Group B, the assessment score was higher for the Moodle group (28.68 ± 4.7) than for the control group (24.26 ± 7.7) (P <  0.01). The questionnaire results showed that students were satisfied with the Moodle platform. Conclusions A specially designed Moodle module may be effective in augmenting the field trip for Chinese herbal medicine education.